Analysis of wood waste composite - Omar Qaiyum, Bin Sulaiman (Universiti Malaysia Sarawak, UNIMAS, 2008)
Wood waste can be economically utilized to generate energy, produce new product or will be disposed. Another alternative is utilizing the wood waste as reinforcement materials to produce a wood waste composite with promising potential. This project investigated the potential of wood waste to produce a composite material by determining the mechanical properties of the composite. Polyester resin and particle of wood waste were used to produce wood waste composite. The specimen preparation and tensile test have been carried out according to ASTM D 3039, the standard method for determination of tensile properties of polymer matrix composite. The result from this project shows that, the wood waste has a potential to produce a composite materials with high tensile strength and high Young’s modulus. The highest tensile strength is achieved with sample A with particle size of 0.0064 mm2 or less at 30% particle volume fraction which is 22.013 MPa while the Young Modulus is 553.003 MPa. The strength of the wood waste composite is also influenced by the size of particle of wood waste. The smaller the size of particles, the inherent flaws will be reduces and tensile strength will increase. The tensile strength of sample A (smaller particle size) is proportional to the increase in volume fraction of particle. Whereby, for tensile strength of sample B is inversely proportional to the increase in volume fraction of particle.